2014
DOI: 10.1080/0309877x.2013.869567
|View full text |Cite
|
Sign up to set email alerts
|

Living and learning as an international postgraduate student at a Midlands university

Abstract: This paper investigates the views of 20 full-time international postgraduate students, many of whom were Chinese, on living, learning and becoming successful students at one university in a multi-cultural city in the Midlands of England. The qualitative study built on findings from the International Students' Barometer (ISB) survey for the university, in that it seeks to understand how students experience of context (living) interacted with their experience of learning in building their identities as successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Research has identified various challenges faced by PhD candidates during their candidature, especially by first year PhD candidates, overseas students, and non-traditional PhD candidates (Busher, Lewis and Comber, 2014;Naidoo, 2015;Wright & Cochrane, 2000). As attention has been given to identifying the most appropriate research methodology for the investigation the PhD candidate may choose to embark upon (Haksever & Manisali, 2000), there are other challenges PhD candidates may encounter during their candidature.…”
Section: Introductionmentioning
confidence: 99%
“…Research has identified various challenges faced by PhD candidates during their candidature, especially by first year PhD candidates, overseas students, and non-traditional PhD candidates (Busher, Lewis and Comber, 2014;Naidoo, 2015;Wright & Cochrane, 2000). As attention has been given to identifying the most appropriate research methodology for the investigation the PhD candidate may choose to embark upon (Haksever & Manisali, 2000), there are other challenges PhD candidates may encounter during their candidature.…”
Section: Introductionmentioning
confidence: 99%
“…Alongside the rise in the recruitment of international students worldwide, there has been an increase in research on the international sojourn. Transition to a new culture marks a significant life event (Kim 2001), calling for a process of adjustment to new cultural norms (Gudykunst 1998;Busher et al 2016;Tarry 2011). Brown and Holloway (2008a) state that adjustment describes the process and outcome of change experienced during the international stay.…”
Section: The International Student Sojournmentioning
confidence: 99%
“…Only seven of the papers reviewed included students from the EU (Bache & Hayton, 2012;Brown & Holloway, 2008;Busher et al, 2016;Goode, 2007;Hockings et al, 2018;Spiro et al, 2012;Taušová et al, 2019). EU students are often classed as 'home' students at UK universities, as they pay the same course fees as domestic students, rather than the increased fees paid by international students.…”
Section: Origin Of the Learnermentioning
confidence: 99%
“…Gu et al (2010) argue that the initial sense of shock largely applied to academic processes. However, Busher et al (2016) contest these findings, arguing that the initial shock experienced by most international students applies as much to the unfamiliarity of living in a new environment as it does to learning. Transitioning to a new environment can include adapting to a new life patterns, food, traditions, values and expectations, all of which can be emotionally and psychologically challenging, leading to feelings of boredom, loneliness and alienation (Gu & Maley, 2008).…”
Section: Challenges Facing International Studentsmentioning
confidence: 99%